Utilization of dexrazoxane in patients treated with doxorubicin: a retrospective, propensity matched analysis of cardiac function and toxicity - Neiman, Zachary M.; Legasto, Carlo S.; Chin, Alan K.; Guan, Tiffany; Schulte, Brian C. (Frontiers in Oncology, 2025)
IntroductionDexrazoxane (DZR) has been used to prevent cardiotoxicity from doxorubicin (DOX), particularly in younger patients with cancer and those with pre-existing cardiac dysfunction. Herein, we sought to further define the role of DZR by evaluating its capacity to mitigate cardiotoxicity in patients actively receiving DOX, while also assessing concomitant toxicities.Materials and methodsWe conducted a retrospective, propensity-matched cohort study at a single academic center, comparing outcomes between patients treated with DZR plus DOX and those who received DOX alone. Patients were matched by age, sex, and cumulative lifetime dose of DOX. Cardiotoxicity was assessed as the change in ejection fraction (EF) during and after treatment. To evaluate associations between DZR and other toxicities, we utilized the Common Terminology Criteria for Adverse Events, Version 5 (CTCAE).ResultsA total of 152 patients were included across both groups. The DOX alone and DOX + DZR groups had median ages of 36 and 28 (ranges 18–68 and 18–69), with median cumulative DOX doses of 375 mg/m2 (ranges 75–525 and 75–600), respectively. Patients were followed up with their last measured EF at a median of −3 and 18.5 days after their final DOX dose, respectively. The median change in EF was −2% in the DOX alone group and −0.7% in the DOX + DZR group (p = 0.9174). Grade 4 anemia occurred in 16 patients in the DOX alone group and in 41 patients in the DOX + DZR group (p = 0.0002). Similarly, grade 4 neutropenia was observed in 15 and 50 patients, respectively (p = 0.0013).DiscussionThe addition of DZR to DOX did not result in a statistically significant change in EF during the treatment window. Given the limitations of the dataset, this may suggest a lack of substantial immediate benefit from the co-administration of DZR with DOX. An increased rate of high-grade neutropenia and anemia was observed in patients receiving the combination, although this may be due to confounding factors. Further analysis is warranted, ideally through larger multi-institutional or prospective studies.